MEJORAMIENTO DE LAS PRÁCTICAS DOCENTES A PARTIR DE PROYECTOS DE INNOVACIÓN - Manuale, Marcela Alicia (Universidad Nacional del Litoral, 2020)
As part of my doctoral thesis entitled “Innovation Processes and Good Teaching Practices”, a progress of the study on innovation projects is here presented. The thesis addresses topics related to teaching processes at the university and their connection with educational innovations, research on practices and learning improvement. Curriculum Innovation Projects (Proyectos de Innovación Curricular, PIC) of the Faculty of Biochemistry and Biological Sciences (Universidad Nacional del Litoral, Argentina), developed during 2017, are studied from a complex and critical perspective. Some reflections will be made from the analysis of the theoretical framework and the data obtained. Although preliminary, it can be said that the processes of design, implementation and evaluation of pedagogical innovations are areas that allow for the improvement of the educational practices, training and the professional development of the faculty.